(untitled) (Journal of School Administration Research and Development, 2016)
Although the assistant principal position has been the career path for aspiring principals, some researchers have claimed the position lacks adequacy as a training position. With limited research available, the purpose of this study was to explore the induction and acclimation experiences of newly assigned assistant principals. Following a phenomenological research approach, interviews were conducted with six public school assistant principals. New assistant principals prepared for their positions by seeking prior leadership opportunities and asking questions, but they noted a lack of confidence in making decisions. These new assistant principals, recognizing the importance of professional relationships, worked to build trust with students and teachers. Implications for school district leaders, preparation programs, and aspiring candidates are provided.